PEMPIs: a new methodology for modeling and prediction of MPI programs performance - Midorikawa, E. T.; Oliveira, H. M. de; Laine, J. M. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2004)
The evaluation and prediction of parallel program performance is becoming more and more important, so that it requires appropriate techniques to identify the factors which influence the application execution time and also the way they interact. In this paper, we present some contributions of our research in this area by describing PEMPIs: a new methodology applied to the analysis and prediction of MPI programs. A new task graph helps us both to understand details of the application and to increase the accuracy of the prediction models. The proposed techniques are detailed and tested through the modeling of a complete application. PEMPIs efficiency has been proved by the results of this application modeling - most tests executed in a cluster of workstations exhibited errors up to 10%.